Terminal drought effect on sugar partitioning and metabolism is modulated by leaf stay-green and panicle size in the stem of sweet sorghum (Sorghum bicolor L. Moench) - Thierry Klanvi Tovignan; Hubert Adoukonou-Sagbadja; Cyril Diatta; Anne Clément-Vidal; Armelle Soutiras; Ndiaga Cisse; Delphine Luquet (CABI Agriculture and Bioscience)
Abstract Background The benefits of leaf stay-green for maintaining grain filling in sorghum under drought was largely demonstrated. However, its role in the stability of a dual production (grain, stem sugar) in tall sweet sorghum remains to be elucidated. This study aimed to analyze the impact of a post-anthesis drought on sugar accumulation along stem internodes in sweet and tall West-African sorghum with variable leaf stay-green and grain yield abilities. Methods Four accessions with similar phenology were studied in two consecutive years in the field at the National Agronomic Research Centre (CNRA) of Bambey (Senegal, West Africa) under two post-anthesis water treatments (irrigated, non-irrigated). Plant morphology, stem sugar related traits, grain production, and plant leaf area (PLA) variation were assessed. Carbohydrate contents (sucrose, hexoses, starch) were determined during grain filling in the whole stem juice and at three internode levels: bottom, median, top. Analysis of variance was performed to test post-anthesis water treatment, accession, organ, year effects and their interactions on the studied traits. Results Panicle dry weight (PDW) was not affected by drought, but strongly varied among years and accessions. The PDW/PLA ratio was negatively correlated with the variation of sucrose and hexoses at the three internodes levels. This carbohydrates reduction was mainly influenced by the PDW. The bigger the panicle the higher the carbohydrates remobilization from the stem to panicle for grain filling. This was mainly shown on accessions G3 and G11 which exhibited low stay green ability. However, G10 with low PDW/PLA ratio and showing higher stay green ability, exhibited a low reduction of total soluble sugars and sucrose and inversely higher increase of hexoses mainly at the median internode. Conclusions This ability to better maintain green leaf area and high hexoses in the stem under post-flowering drought could be an osmoregulation mechanism to adapt to drought. Therefore, stay-green is an important trait to consider for sweet sorghum breeding and particularly in the objective of developing dual purpose varieties in drought prone environments.